2011
DOI: 10.1007/s00228-011-1130-4
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of pharmacy-initiated pharmacogenetic screening for CYP2D6 and CYP2C19

Abstract: PurposeOur purpose was to investigate the feasibility of pharmacy-initiated pharmacogenetic (PGt) screening in primary care with respect to patient willingness to participate, quality of DNA collection with saliva kits, genotyping, and dispensing data retrieved from the pharmacy.MethodsPolypharmacy patients aged >60 years who used at least one drug with Anatomical Therapeutic Chemical (ATC) code N06AA01–N06AX19 (antidepressants), A02BC01–A02BC05 (proton-pump inhibitors), N05AA01–N05AH04 (antipsychotics), or C0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…The time seemed to be well spent, given that the majority of patients (54%) consented to PGx testing and agreed to participate in the study once they learned more about PGx. As demonstrated by other studies, 31,32 this finding suggests that patients empowered with knowledge about PGx are receptive to undergo PGx testing, which could improve their medication management. Further, this indicates that either prescribers need to have sufficient time to educate patients on PGx before testing, or will need to implement a consult-based service, such as ours, and allow a pharmacist to provide this education.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The time seemed to be well spent, given that the majority of patients (54%) consented to PGx testing and agreed to participate in the study once they learned more about PGx. As demonstrated by other studies, 31,32 this finding suggests that patients empowered with knowledge about PGx are receptive to undergo PGx testing, which could improve their medication management. Further, this indicates that either prescribers need to have sufficient time to educate patients on PGx before testing, or will need to implement a consult-based service, such as ours, and allow a pharmacist to provide this education.…”
Section: Discussionsupporting
confidence: 61%
“…This target sample size was estimated as sufficient to assess feasibility, as previous pharmacist-physician collaborative studies and pharmacist-led PGx studies have demonstrated implementation feasibility with similar sample sizes. 23,[27][28][29][30][31][32] In March 2016, the research pharmacist began reviewing charts of the practice sites' electronic health records to determine potentially eligible patients, and in April 2016, enrollment commenced. When the research pharmacist was on site, she collaborated with staff to introduce the consent process to potentially eligible patients and to ascertain whether these patients were experiencing any MRPs around the time of the scheduled PCP appointment.…”
Section: Patient Enrollmentmentioning
confidence: 99%
“…22 We have shown that it is possible for both family physicians and pharmacists to obtain saliva samples from patients, send the samples to the laboratory, complete the biophysical and laboratory data needed for an MDSS and make decisions based on individualized medication options. In a pharmacybased study (n = 54) by Swen and colleagues, 23 9 saliva samples (16.7%) contained too little DNA, whereas we had 1 sample (0.5%) that contained too little DNA. We achieved an overall call rate of 99%, compared with Swen and colleagues' call rates of 93.3% and 100% for CYP2D6 and CYP2C19, respectively.…”
Section: Discussionmentioning
confidence: 89%
“…They found that approximately 60% of patients consented to the testing; a high percentage considering the screening was not directly related to their clinical treatment. Their study provided evidence for pharmacy-initiated pharmacogenetic screening to be feasible in a primary care setting (148). A retrospective pilot study by Mü ller et al examined 35 patients with schizophrenia genotyped for CYP2D6 and CYP2C19 metabolizer status using the Amplichip † test.…”
Section: Pharmacodynamicsmentioning
confidence: 99%